Cocooning against COVID‐19: The argument for vaccinating caregivers of patients with cancer. Issue 16 (23rd April 2021) - Woodfield, Maresa C.; Pergam, Steven A.; Shah, Parth D.
Abstract : Current national COVID‐19 vaccination guidelines and recommendations focus vaccine guidance on patients with cancer. In this COVID‐19 vaccination race, "cocoon vaccination" strategies, which include informal caregivers and household contacts as priority groups for SARS‐CoV‐2 vaccination, could be an additional strategy used to protect patients with cancer who may have limited immune responses to current vaccinations. Medical systems specializing in cancer care should support education and vaccination campaigns which target informal caregivers and household contacts in addition to cancer patients.